Successful Pregnancy in Post-traumatic Splenosis Woman: A rare condition - Siriwan Srisuwan; Tharangrut Hanprasertpong (The Royal Thai College of Obstetricians and Gynaecologists, 2021)
Splenosis is a rare benign condition which was first described in 1929. Most of cases found in men following the splenic rupture without symptom. A successful pregnancy in a splenosis woman has never been reported in English literatures. Herein we experienced a first case of a successful pregnancy in splenosis woman. She was successfully delivered a healthy male infant by Cesarean delivery using a Pfannenstiel skin incision.